1994
DOI: 10.1021/jf00043a018
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Isolation of Lolitrem B and Structure Determination of Lolitrem E

Abstract: A method for isolation of hundreds of milligrams of lolitrem B is reported. Lolitrem E, the most abundant of the minor lolitrems, was isolated from side fractions and its structure determined by mass spectrometry and one-and two-dimensional NMR techniques. Lolitrem E differs from lolitrem B in being an ether, rather than an acetal, derivative of lolitriol. Evidence is presented that the compound previously isolated by Gallagher and co-workers, and assigned the structure of lolitrem C, was in fact lolitrem E. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 6 publications
3
73
0
Order By: Relevance
“…Lolitrem B was extracted from ryegrass seed infected with Neotyphodium lolii and purified by chemical methods as described previously (Miles et al, 1994). The resulting crystalline solid was shown to be at least 97% pure by NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lolitrem B was extracted from ryegrass seed infected with Neotyphodium lolii and purified by chemical methods as described previously (Miles et al, 1994). The resulting crystalline solid was shown to be at least 97% pure by NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of tremor induced by the toxins was measured using a previously described mouse bioassay method (Gallagher and Hawkes, 1986). This bioassay has been used extensively in our laboratories during structure-activity studies of tremorgenic toxins (Miles et al, 1992(Miles et al, , 1994Munday-Finch et al, 1997). Toxins were administered by intraperitoneal injection as a solution in 9:1 (v/v) dimethyl sulfoxide (DMSO)-water (50 l).…”
Section: Methodsmentioning
confidence: 99%
“…Quantification was achieved by comparison with a pure standard (Miles et al 1994). The limit of quantitation for this technique is 0.1 mg/kg.…”
Section: Endophyte Alkaloid Analysismentioning
confidence: 99%
“…The absence of lolitrems in many epichloë endophyte-grass associations does not appear to be due to a grass host effect but rather to the inability of the endophyte to produce the compound (5, 63). Until recently, genetic analysis of the genes required for the production of lolitrem B was not available, so a large effort was put into the chemical analysis of endophyte-infected grasses that resulted in the identification of indole-diterpene compounds, such as lolitriol, lolicines A and B, lolilline and terpendole M, predicted to be precursors or by-products of lolitrem B biosynthesis (5,19,37,38,40,(46)(47)(48)(49). These analyses showed that the ability to produce the alkaloids was dependent on the presence of the endophyte within the plant.…”
mentioning
confidence: 99%